Repositórios de objetos de aprendizagem para o ensino de ciências e mediação por tecnologias da informação e comunicação - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The present work represents the effort to reconcile the area of Information and Communication Technology (ICT) with the area of Education, especially Science Education. The convergence between the themes of ICTs, Science Teaching and Learning Objects Repositories compose the scenario of this research. From the perspective of an action research, it was proposed to develop a Repository of Learning Objects using the DSpace platform, verifying the viability of its use by primary education teachers, as well as the learning objects stored in them as tools capable of contributing to the teaching-learning process. From a literature review, the need to use ICTs in education was glimpsed and it was possible to perceive that the repositories can represent advantages for teachers to have access to multimedia content, learning objects and other educational resources contributing with their pedagogical practices. The idea behind the developed repository is to allow the community interested in the production and use of these learning objects to collaborate in the feeding of the repository so that this environment serves to enhance the teaching of science and provide another alternative for the insertion of ICT in school education. The study points to the imminent need to use learning objects, increasing student demand, the need for continuing teacher training, the interest of teachers in the use of ICTs in pedagogical mediation, the need for investments in infrastructure in schools and the provision of repositories for the effective storage and management of learning objects.
Learning objects repositories for sciences teaching and information and communication technologies mediation
Keywords: DSpace; Repositório de Objetos de Aprendizagem; TICs na Educação; Objetos de Aprendizagem; Ensino de Ciências; DSpace; Repository of Learning Objects; ICT in Education; Learning Objects; Science Teaching; CIENCIAS EXATAS E DA TERRA